At the temple gates: the religion of freelance experts in the Roman Empire - Wendt, Heidi (Oxford University Press, 2016)
In this book Heidi Wendt studies the activities of 'freelance' religious experts in first-century Rome, such as oracles and magi, and makes a case for their influence on religious teachings that gave rise to many new religious movements, including Christianity.